Puristababy / Muhammad Hariz Hashim, Anis Nedya Ramli and Muniira Mazlan - Hashim, Muhammad Hariz; Ramli, Anis Nedya; Mazlan, Muniira (2017)
The team is developing a baby stroller, a concept baby stroller that creates pure and clean microclimate for your baby. Inspired by a car that recirculates the inside air instead of outside unless you set it up to do so. This baby stroller purifies the air inside using a special designed filter and recirculate to protect your baby from polluted air. The glass lid works as a shield as protection from UV rays where parents can still communicate with their baby through a speaker, there's a built-in microphone inside the stroller. Parents can always mute the sound just in case the baby's sleeping. A product concept testing with a survey conducted among 40 classmate shows that when the concept is available in market, this device is conveniently for family that has a kid and toddles. The concept will be tested with three families that have a kids and once product is ready, the product will be test at the market.